Differential Diagnosis of Pain Phenomena in the Residual Limb (Literature Review) - Turchyn, O.A.; Piatkovskyi, V.M.; Yevlantieva, T.A.; Kharchyk, V.S.; Liabakh, A.P. (TERRA ORTHOPAEDICA, 2025)
Objective. Analysis of the literature devoted to etiology and pathogenesis, clarification of definitions, and differential diagnosis of pain phenomena in the residual limb.Materials and Methods. This publication is a descriptive literature review based on an analysis of available literature sources retrieved from library databases of the National Library of Ukraine named after V.I. Vernadsky, PubMed, and the Cochrain Database.Results and Discussion. Conclusions. Pain phenomena in the residual limb include phantom limb pain, phantom limb sensations, and stump pain. One type of pain may progress into another and be aggravated by a third, which complicates their diagnosis and the choice of treatment methods. Phantom limb pain is the most common; it is the main cause of physical limitations and disability, tends to become chronic, is difficult to treat, and affects the quality of life. The pathogenesis is complex and is associated with functional reorganization in the primary somatosensory cortex. The current literature on the topic is quite fragmented and contradictory. The studies presented do not characterize the current patient population, which has significantly changed over the past few years. This highlights the need for further study of the issue.